Engaging with local communities: Five key lessons that businesses can learn from universities. Issue 3 (June 2021) - Misra, Debananda; Pinheiro, Rómulo
As businesses are coming to terms with the challenges derived from the Covid-19 crisis, they are realizing the need to do more for and with their local communities than being co-located or having business relationships. Business leaders are learning that engaging with local communities can be helpful in steering their business through crises and helping to prepare for the future. The central idea of this article is that businesses can learn from universities about engaging with local communities. It outlines five key lessons, illustrating them with examples and relating them to key concepts and perspectives from the literature. The emphasis in these lessons is on their potential to make businesses self-reliant, socially responsible and resilient. As businesses look for lessons, frameworks and best practices for engaging with their communities during and after a significant crisis, these five lessons from universities can point them toward new directions that would be hard to find within the business community. The lessons can be used by business leaders to design initiatives and implement policies and practices for engaging with their local communities in ways that are mutually beneficial and promote long-term sustainability.